Analogical education in times of virtuality: Back to the hands-on activities – 15 years of NASE program - Garcia, Beatriz Elena (2025)
The interplay among emerging technologies, including artificial intelligence, and creative activities that involve engaging not only thought or the brain, but also the entire organism to produce a product, such as creating 3D models through cutting, pasting, and assembling, and then using those models to analyze natural phenomena, to verify and ultimately comprehend the relationship between the two, is a central theme of our time. This presentation showcases a few simple, albeit insufficient, examples to illustrate the importance of returning to activities that we can associate with the “main-à-la patte” or “hands-on” actions. The discussion of how to integrate new technologies into problem-solving and leverage their potential to enhance our understanding of the natural world, while ensuring that any formal or informal activity at this inflection point of human existence is “user-centered” in universal terms, is also explored.